ANALISIS PENDAPATAN DAN KEBERLANJUTAN USAHA BUDIDAYA IKAN SIDAT DI DESA KRATON KECAMATAN YOSOWILANGUN KABUPATEN LUMAJANG - Rizky Eka Aulia; Ati Kusmiati; Triana Dewi Hapsari (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
The utilization rate of eel fish locally (in the country) is still very low, this is because many people still not familiar with this fish yet. Most of the population in Indonesia is still not familiar to consume an eel fish. Until now, the supply of eel fish seeds is still dependent on catching in nature. The condition of income decline experienced by eel fish farmers in the Kraton village, made changes to the production results caused by the price of eel fish that is still not affordable by the community. This change will have an impact on the sustainability of the eel fish cultivation business in Kraton village in Yosowilangun sub-district, Lumajang district. This study aims to know the income of eel fish farmers and the eel fish cultivation business sustainability. This study applied analysis of income and the sustainability of the Rapfish with the descriptive method. The results showed that (1) the eel fish farmers at Kraton village in Yosowilangun sub-district, Lumajang district earn income, (2) the status of sustainability of cultivation is at simply continues on dimension of ecological, social, economic and institutional.